Doryphoribius chetumalensis sp. nov. (Eutardigrada: Isohypsibiidae) a new tardigrade species discovered in an unusual habitat of urban areas of Mexico - Pérez-Pech, Wilbert Andrés; Anguas-Escalante, Abril; Cutz-Pool, Leopoldo Querubin; Guidetti, Roberto (Zootaxa, 2017)
A new species, Doryphoribius chetumalensis, is described from specimens collected in the city of Chetumal (Quintana Roo state, Mexico). The species was found in a new and unusual habitat for urban tardigrades, i.e. the soil sediment accumulated on the border of streets. This discovery shows that tardigrades can live in this habitat, demonstrating once again the wide capacity of this taxon to tolerate adverse habitats, and to survive in environments with high anthropogenic impact. Doryphoribius chetumalensis sp. nov. differs from all the other species of the genus in having enlarged and wide bulbous base of the claws. Within Doryphoribius, it belongs to the zappalai group, and differs from the species in this group, not only in the claw shape, but also by the orange body colour, the smooth cuticle, the absence of a tooth in the wall of the buccal ring, and the absence of lunules under the claws. This is the first record of tardigrades, identified to species level, in Quintana Roo state. A taxonomic key of the Doryphoribius genus is also presented.